Ethnopharmacological Study on Nigella Sativa Seeds Extracts: Pharmacognostical Screening, Abortifacient Potential and its Evolution Parameters - Alamoudi, Mariam K.; Almehmadi, Khulood A.; Ali, Md Sajid; Hashmi, Sana; Alharbi, Mohammed Fulayyih Essa; Rashid, Mohammad; Athar, Md Tanwir; Khan, Shamshir; khaja, Samiuddin; Akhtar, Naseem (Migration Letters, 2023)
Current research investigates the feticide properties of Nigella sativa, a natural alternative to pharmaceutical feticides such as mifepristone. Abortion induced by mifepristone is often accompanied by distressing side effects, prompting the exploration of safer alternatives. Nigella sativa seeds were processed into coarse powder through grinding and subjected to ethanolic and aqueous extractions. Pregnant mice were administered extracts at 400 milligrams per kilogram of body weight, with a comparison group receiving 2.85 mg/kg p.o. of mifepristone. The study showed a significant decrease in fetal survival rates with nigella sativa extract treatment with the untreated control group exhibiting a 100% survival rate and the 400 mg/kg p.o. Dose groups showed rates of 26.66% for aqueous extract and 33.33% for ethanolic extract. Importantly, none of the fetuses in the mifeprin-treated group survived. The results indicate a promising 70% abortion rate with well-tolerated doses of Nigella sativa extracts, highlighting the potential for natural alternatives to mitigate the side effects associated with mifepristone administration. This research underscores the importance of exploring botanical sources for safer and more tolerable options in induced abortion.